2014
DOI: 10.1074/jbc.m114.586891
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis Determining Inhibition/Activation of Nociceptive Receptor TRPA1 Protein

Abstract: Background: Nociceptive TRPA1 is an important drug discovery target for identification of analgesics. Results: A967079, one of the most potent mammalian TRPA1 antagonists, showed marked species differences. Conclusion: A single amino acid was responsible for inhibitory/stimulatory actions of A967079. Significance: The present data provide novel insight in the search for analgesics targeting TRPA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Many research groups, including our own, have previously attempted to identify the binding mechanisms or the effective sites for potent mammalian TRPA1 antagonists. While the action sites of A96 and AP-18, which are structurally similar, were discovered912131425, those of HC remained undetermined. It is well documented that the effects of TRPA1 antagonists differ in a species-specific manner; therefore, we utilized these species-specific differences to identify the sites of the antagonistic activity of HC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many research groups, including our own, have previously attempted to identify the binding mechanisms or the effective sites for potent mammalian TRPA1 antagonists. While the action sites of A96 and AP-18, which are structurally similar, were discovered912131425, those of HC remained undetermined. It is well documented that the effects of TRPA1 antagonists differ in a species-specific manner; therefore, we utilized these species-specific differences to identify the sites of the antagonistic activity of HC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this species diversity, comparative analysis of TRPA1 among different species has proven informative for understanding structure-function relationships89. For example, A967079 (A96) and AP18, both of which are structurally similar, are potent mammalian TRPA1 antagonists, although their inhibitory effects on TRPA1 vary among species101112. Comparative and mutagenesis experiments with TRPA1 from different species revealed that several amino acids in the TM5 domain are crucial to the effects of these two antagonists91213.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 (B) Structures of a tetrameric (inset) or a single subunit of human TRPA1 are shown with critical amino acids involved in activation or inhibition by A-967079, HC-030031, and methyl anthranilate highlighted in cyan, magenta, and green, respectively. 11,52,63,69,70,72 Critical amino acids involved in TRPA1 sensitivity to MA were identified using chicken TRPA1. 52 TM, transmembrane domain; PH, pore helix; ARD, ankyrin repeat domain.…”
Section: Thermosensitive Transient Receptor Potential Channels As Thementioning
confidence: 99%